Ideologies and mass violence : the justificatory mechanics of deadly atrocities - Leader Maynard, J (2014)
This thesis seeks to provide an account of the role played by ideologies in acts of mass violence against civilians, such as genocides, murderous state repression, war crimes, and other ‘atrocities’. Mass violence of this kind has already received extensive study, with scholars frequently emphasising their belief that ideology is important. Until now, however, discussions of ideology have been held back by a lack of conceptual and theoretical development, leading to narrow portrayals of ideology’s role, vagueness over its relevance, and dubious assumptions about its theoretical implications. This thesis addresses these problems by building a more focused and integrative theoretical framework for analysing the ideological dynamics of atrocities. I engage in an extensive conceptual and methodological discussion, to establish the best way of defining and utilising the concept of ideology. In doing so, I emphasise how ideology can be important even for that majority of atrocity perpetrators who do not meet classic but misleading stereotypes of fanatical killers driven by burning hatred. I then detail my actual account of the ideological dynamics of deadly atrocities, which centres around the identification of six ‘justificatory mechanisms’: dehumanisation, guilt-attribution, threat-construction, deagentification, virtuetalk, and future-bias. These justificatory mechanisms describe sets of ideological processes that recur across different cases of violence against civilians, and which make that violence look permissible or even desirable to those who, in a variety of roles, carry it out. I then substantiate this account through three case studies: of Nazi atrocities, Stalinist oppression, and Allied area bombing in World War II. These cases demonstrate the cross-case applicability of the six justificatory mechanisms, and illustrate how the framework I offer allows us to construct more causally explicit, psychologically plausible, and comprehensive pictures of the way key ideologies feed in to the most destructive campaigns of violence against civilians.